"Your Young Lesbian Sisters": Queer Girls' Voices in the Liberation Era. Issue 1 (1st March 2019) - Littauer, Amanda H.
Abstract : Drawing on letters and essays written by teenage girls in the 1970s and early 1980s, and building on my historical research on same-sex desiring girls and girlhoods in the postwar United States, I ask how teenage girls in the 1970s and early 1980s pursued answers to questions about their feelings, practices, and identities and expressed their subjectivities as young lesbian feminists. These young writers, I argue, recognized that they benefitted from more resources and role models than did earlier generations, but they objected to what they saw as adult lesbians' ageism, caution, and neglect. In reaching out to sympathetic straight and lesbian public figures and publications, girls found new ways to combat the persistent isolation and oppression faced by youth whose autonomy remained severely restricted by familial, educational, and legal structures.